Quercetin Enhances Inhibitory Synaptic Inputs and Reduces Excitatory Synaptic Inputs to OFF- and ON-Type Retinal Ganglion Cells in a Chronic Glaucoma Rat Model - Zhou, Xujiao; Li, Gang; Yang, Boqi; Wu, Jihong (Frontiers in Neuroscience, 2019)
Background Glaucoma is a neurodegenerative disease caused by excitotoxic injury of retinal ganglion cells (RGCs). In our previous model of high intraocular pressure, prepared by injecting magnetic beads into the anterior chamber, we demonstrated that an important natural dietary flavonoid compound (quercetin) can improve RGC function. However, it is unclear whether quercetin can improve the synaptic function of RGCs and how quercetin regulates synaptic transmission in rat models of chronic glaucoma. Methods A rat model of chronic glaucoma was prepared by electrocoagulation of the superior scleral vein. Electrophysiological electroretinography was used to detect the photopic negative response (PhNR). The whole-cell patch-clamp technique was used to clamp ON- and OFF- type RGCs in sections from normal retinas and from retinas that had been subjected to glaucoma for 4 weeks. Results Quercetin can reverse the decrease in PhNR amplitude caused by chronic glaucoma. The baseline frequency of miniature GABAergic inhibitory postsynaptic currents (mIPSCs) in the RGCs of glaucomatous retinal slices was lower than that of the control group. The frequencies of miniature excitatory postsynaptic currents (mEPSCs) were not significantly different between control and glaucomatous RGCs. The baseline frequencies of GABAergic mIPSCs and mEPSCs in OFF-type glaucomatous RGCs were greater than those in ON-type glaucomatous RGCs. Quercetin increased miniature GABAergic inhibitory neurotransmission to RGCs and decreased miniature glutamatergic excitatory neurotransmission, reducing the excitability of the RGCs themselves, thus alleviating the excitability of RGCs in glaucomatous slices. Conclusion Quercetin may be a promising therapeutic agent for improving RGC survival and function in glaucomatous neurodegeneration. Quercetin exerted direct protective effects on RGCs by increasing inhibitory neurotransmission and decreasing excitatory neurotransmission to RGCs, thus reducing excitotoxic damage to those cells in glaucoma.